Kernel function-based interior-point algorithms for linear optimisation - Bounibane, Bachir; Djeffal, El-Amir (International Journal of Mathematical Modelling and Numerical Optimisation, 2019)
We propose a primal-dual interior-point algorithm for linear optimisation based on a class of kernel functions which is eligible. New search directions and proximity measures are defined based on these functions. We derive the complexity bounds for large and small-update methods respectively. These are currently the best known complexity results for such methods.